Boredom and Addiction: An exploratory view at university students' digital game playing processes in leisure time - Nazlı Deniz Öz; Abdil Arı (Selcuk University, 2023)
The concept of leisure time, which has attracted the attention of scientists from the past to the present, appears in many areas of life. In today's world, the busy pace of work, the epidemic process we are in and the many difficulties experienced once again emphasize the importance of effective use of time. At this point, individuals who cannot use their free time effectively and efficiently are likely to experience the perception of boredom with exposure to restrictions. The rapidly developing technology has brought with it many innovations such as computers and the internet, which have become an inseparable part of our lives. For this reason, technology, which has been developing rapidly in recent years, has brought many innovations such as computers and the internet, which have become an inseparable part of our lives. Thus, over time, a huge sector has been formed on the axis of digital games, and digital games continue to increase their popularity in the world with phenomena such as e-sports. In the process, digital games are developed to become more refined for the motivation of individuals to play digital games, increasing their addictive effects. In this direction, in our study, the relationship between our young people's perception of being bored in leisure time and digital game addiction, which is one of the valuable building blocks of the future, will be investigated.